Spatio-temporal variation of water requirement and meteorological impact factors of maize Shaanxi, China - Duan, Jingjing; Zhao, Jing; Sun, Geyao; Gao, Feng (Frontiers in Environmental Science, 2023)
To quantitatively reveal the characteristics of the spatial and temporal distribution and the influencing factors of the maize water requirement in Shaanxi Province, the Penman-Monteith model and path analysis were used to systematically analyze the interannual variation and spatial distribution of the maize water requirement at different growth stages in three climatic zones in Shaanxi Province. And the relationship between the water requirement and meteorological factors based on daily meteorological data in Shaanxi Province for the past 60 years. The results showed that the maize water requirement during the whole growth period decreased from 1960 to 1989, with a rate of change of -2.08 mm / a, increased from 1989 to 2019, with a rate of change of 0.38 mm / a, and decreased from 1960 to 2019, with a rate of change of -0.46 mm / a. The water requirement of maize decreases from north to south during the whole reproductive period. That of seedling and male stage are more in the Guanzhong, followed by the north and the least in the south. The water requirement of maize at jointing stage increased from north to south. And the water requirement distribution is more in the north, followed by the south and the least in the Guanzhong area during the maturity period. The average temperature and the duration of the sunshine are the key factors that affect maize water requirement in Shaanxi Province, and have an increasing effect on water requirement, wind speed has an increasing effect on water requirement but is not obvious, water vapor pressure and relative humidity have an inhibiting effect on water requirement. For spring maize, the promoting effect of the duration of the sunshine on maize water requirement was gradually strengthened from north to south. The promoting effect of mean temperature and wind speed decreased gradually. The inhibitory effect of water vapor pressure and relative humidity decreases continuously. This study can provide a scientific basis for the management of irrigation quota in maize growing areas under similar cropping conditions.